2020
DOI: 10.1111/micc.12648
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, classification, and MRI parallels in microvascular disease of the heart and brain

Abstract: Small vessel disease of the brain and the heart has far-reaching clinical implications, with healthcare costs totaling billions each year. 1-3 Though a lack of consensus in the classification of small vessel disease exists, the pathophysiologic features implicate damage to small end arteries, arterioles, venules, and capillaries, resulting in chronic end-organ hypoperfusion. 4 In the brain, hypoperfusion can contribute to cognitive decline, gait disturbance, dementia, and stroke; in the heart, hypoperfusion ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 128 publications
0
7
0
Order By: Relevance
“…Magnetic Resonance Imaging (MRI) stands out as a highly auspicious neuroimaging technique employed in contemporary clinical environments [13,14]. It plays a pivotal tool in generating diagnostic medical images of the human brain, showcasing its vital role in accurately identifying pathological conditions in the central nervous system (CNS) [15,16,17,18]. However, susceptibility artifacts in MRI, arising from varying magnetic susceptibilities of adjacent tissues or substances, can cause distortions in images of the OFC.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) stands out as a highly auspicious neuroimaging technique employed in contemporary clinical environments [13,14]. It plays a pivotal tool in generating diagnostic medical images of the human brain, showcasing its vital role in accurately identifying pathological conditions in the central nervous system (CNS) [15,16,17,18]. However, susceptibility artifacts in MRI, arising from varying magnetic susceptibilities of adjacent tissues or substances, can cause distortions in images of the OFC.…”
Section: Introductionmentioning
confidence: 99%
“…Since microcirculation represents the ‘mesoscale’ functionally bridging the systemic circulation to perfused tissues, microvascular dysfunction (MVD) ultimately compromises oxygen delivery to the end organ(s). 121 Indeed, it is within the microcirculation that the earliest signs of several cardiovascular diseases manifest themselves. For example, the Firefighters and Their Endothelium (FATE) study 8 showed that microvascular health represents a powerful independent predictor of cardiovascular events in primary prevention.…”
Section: Introductionmentioning
confidence: 99%
“…CT can assess CBF and in CSVD patients, but MRI is the preferred method [ 50 ] as it provides an enhanced soft-tissue assessment and estimation of CBF in a single comprehensive study without ionizing radiation and possible administration of iodine contrast medium. PET does not have the ability to identify the morphological features of CSVD; it does, however, have a broad evidence base for estimating CBF [ 51 ] and other related measures and can be useful in distinguishing CSVD from Alzheimer’s and other neurodegenerative pathology [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although HFpEF and CSVD may differ in response to basally required blood flow, they share a significant similarity when it comes to measuring endothelial function in the form of cerebral vascular reserve (CVR) [ 51 ]—the ratio between stress and rest CBF analogous to MPR in the heart. As endothelial dysfunction is likely a key pathophysiological mechanism in the development of CSVD, assessing it through CVR measurement may be advantageous in CSVD evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation